2003
DOI: 10.1159/000074884
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin Stress Response but Not Glucocorticoid-Negative Feedback Is Altered by Prenatal Morphine Exposure in Adult Male Rats

Abstract: The present study was designed to investigate the effects of prenatal morphine exposure on the hypothalamic-pituitary-adrenal (HPA) axis-regulated stress responses by measuring restraint stress-induced changes in the adrenocorticotropic hormone (ACTH) and corticosterone (CORT) levels. In experiment 1, plasma levels of ACTH and CORT in prenatally morphine-, saline-exposed and control male rats were determined before and at several times after restraint stress. There were no statistically significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
6
24
0
2
Order By: Relevance
“…Therefore, it is important to note that prenatal opiate exposure followed by postnatal withdrawal diminished the stress axis response to immunological and social stressors in neonatal rats, whereas in adulthood, an exaggerated response was detected (Hamilton et al, 2005). The adrenocorticotropin (ACTH, the hypophyseal component of the stress response) and corticosterone (a rodent glucocorticoid in the adrenal cortex) responses are dissociated (Rimanoczy et al, 2003;Slamberova et al, 2004). Although there were no differences in basal levels between control animals and intra-and postnatal morphine-treated animals, stressor-induced ACTH elevations were smaller in the opioid-exposed groups.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Therefore, it is important to note that prenatal opiate exposure followed by postnatal withdrawal diminished the stress axis response to immunological and social stressors in neonatal rats, whereas in adulthood, an exaggerated response was detected (Hamilton et al, 2005). The adrenocorticotropin (ACTH, the hypophyseal component of the stress response) and corticosterone (a rodent glucocorticoid in the adrenal cortex) responses are dissociated (Rimanoczy et al, 2003;Slamberova et al, 2004). Although there were no differences in basal levels between control animals and intra-and postnatal morphine-treated animals, stressor-induced ACTH elevations were smaller in the opioid-exposed groups.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Antenatal opiate exposure affects brain development 9,10 with resulting decreases in corticogenesis, neurogenesis, and synaptogenesis 11,12 and alterations in the ontogeny of the stress axis [13][14][15] and immune response. 16 Human studies also allude to the association of prenatal opiate exposure and small head circumference [17][18][19][20] and decreased brain volumes found on imaging.…”
Section: What's Known On This Subjectmentioning
confidence: 99%
“…Recently, we [2]demonstrated that prenatal morphine exposure diminishes the stress-induced increase in adrenocorticotropic hormone (ACTH) plasma concentration and delays the return of ACTH to basal level in male rats. Basal levels of ACTH, however, did not differ between morphine- and saline-exposed males [2]. In addition, there was no effect of prenatal morphine exposure on basal or stress-induced corticosterone (CORT) levels [2].…”
Section: Introductionmentioning
confidence: 99%